Peningkatan Motivasi dan Keterampilan Membaca Permulaan Siswa Kelas I Melalui Media Aplikasi Bamboomedia BMGames Apps: Improving Motivation and Beginning Reading Skills of Class I Students Through Bamboomedia BMGames Apps . Media Applications - Hasanudin, Cahyo; Puspita, Erna Linda (Universitas Muhammadiyah Sidoarjo, 2017)
This study aims to (1) describe the application of media Bamboomedia BMGames apps application smart reading can increase the motivation and skills to read the beginning of the first-class students MI Muhammadiyah 27 Geger, (2) to increase the motivation and skills to read the beginning of the first-class students MI Muhammadiyah 27 Geger using media bambomedia BMGames apps application smart reading. This study is a class action (Classroom Action Research). Data collection techniques used were observation, interviews, questionnaires, documentation, and testing. Data analysis techniques used comparative descriptive techniques and critical analysis. The conclusions of this study were (1) the application of media Bambomaedia BMGames Apps application smart reading in learning to read the beginning of the class I MI Muhammadiyah 27 Geger can increase the motivation and skills of students in each indicator in the cycle I and II, (2) increase student motivation in learning to read the beginning can be seen from pre action average of 54.67%, the first cycle, and the cycle II 72.00%, 81.33% medium, the student's skills in reading increased from the beginning pre action average of 59.33% and then in the first cycle, 71.33 % and the second cycle, 85.33% have reached the limit of completeness (KKM ≥ 70).